PEMODELAN DAN OPTIMASI PENGUATAN KUALITAS LAYANAN GURU - Noor Sjahid; Rais Hidayat; Soewarto Hardhienata (JURNAL MANAJEMEN PENDIDIKAN, 2021)
IMPROVING ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) THROUGH STRENGTHENING EMOTIONAL INTELLIGENCE AND TEACHER JOB SATISFACTIONService quality is a management resource that is very important to be considered in order to achieve the goals of national education. However, the preliminary survey results indicated that the quality of teacher services were still needed to be improved. The aim of this study was to find efforts to improve teacher service quality (Y) just like the  research theme which was through a study of the influencing power between the independent variables of Job Satisfaction (X1) and Work Motivation (X2) and Proffessional Commitment (X3) as an intermediary variable (intervening). . This research was conducted at 12 private senior high schools in Cibadak commissariat, Sukabumi regency, where the total research object was 109 permanent teachers. The implemented research approach was the POP-SDM approaching that was modeling and optimization of management resources strengthening. POP-SDM was to combine the qualitative researches inorder to find out the constellation of influencies among the variables, the statistical mathematical models to improve the quality of teacher services and the determination of research hypotheses and quantitative research to prove the research hypothesis generated in the qualitative research. The research method used was a path analysis to determine the influence among the variables studied and Sitorem analysis for indicator analysis. The results of the study resulted in a service quality improvement model where the mathematical model was Ŷ = 0.217X1 + 0.451X2 + 0.40X3 + 0.647 wheather X1   was the teacher job satisfaction, X2 was the teacher work motivation  and X3 was professional commitment. While the optimal solution found out that there were 3 indicators which already satisfied so that they were only needed to be maintained or developed. They were consists of achievement, seriousness in carrying out their duties, and emotional bonding to the profession. Beside that, there were 22 indicators that were still weak so that they were needed to be improved where the improvement order of priority were as follows: responsibility, progression, organizational procedures, working conditions, recognition, status, rewards, benefits, loyalty, opportunities, dedication, working atmosphere, type of work, supervision, coworker support, salary, promotion opportunities, responsiveness, assurance, reliability, empathy and direct evidence.